The eyes of the wall : space, narrative and perspective - Baasch, Rachel Mary (Rhodes University, Faculty of Humanities, Department of Fine Art, 2013)
The Eyes of the Wall and Other Short Stories is concerned with dialectics of seeing and perceiving as they pertain directly to a corporal understanding of interiority and exteriority, architectural framing and notions of dislocation in relation to place. This practical submission is a site-specific installation that engages in a reciprocal dialogue with its environment. The individual sculptural works which demarcate the parameters of the installation are hybrids of domestic architectural forms, (namely the wall, the window and the door) and internal furnishings such as the curtain and the bed. These hybridised metal and resin constructions frame the interior of a site, a tennis court located within my immediate Grahamstown environment. The placement of familiar objects generally associated with the home and notions of security and privacy, within the open, exposed and permeable enclosure of the tennis court evoke a sense of displacement within the viewer. This supporting document, The Eyes of the Wall: Space, Narrative and Perspective, considers the key conceptual concerns informing my installation. In this mini-thesis I address the relationship between domestic architecture and the body, examining the notion of framing as fundamental to the individual comprehension of space. I position my work in relation to that of Mona Hatoum drawing on the similarities that exist between her practice and my own. In the first chapter of this paper: My House/Your House: Walls, Windows, Doors and Skins I address the relationship between domestic architecture, framing and the body, and 'contamination'. Within Chapter Two: Narratives of Division I engage with the idea of multiple 'short stories'"”personal and collective narratives"”and their connection to issues of division and dislocation. Chapter Three: Seeing Blindness discusses the possibility that perspective, or at least one potential approach to perspective is concerned with that which one cannot see, an acknowledgment of the implicit relationship between seeing and not-seeing. Each of the three core concerns expressed in the title of this mini-thesis, The Eyes of The Wall: Space, Narrative and Perspective intersect within the site of The Eyes of The Wall and Other Short Stories. It is at this intersection that the shadows of stories within stories within stories insert themselves, like phantom limbs into the gaps and tensions framed by the forms of the installation.
Keywords: Installations (Art); Frames (Sociology); Architecture, Domestic, in art; Narrative art